Lung transplantation from donation after circulatory death, evolution, and current status in the United States. Issue 3 (2nd January 2023) - Furukawa, Masashi; Noda, Kentaro; Chan, Ernest G.; Ryan, John P.; Coster, Jenalee N.; Sanchez, Pablo G.
Abstract: Background: The number of lung transplants from donors after circulatory death has increased over the last decade. This study aimed to describe the evolution and outcomes following lung transplantation donation after circulatory death (DCD) and report the practices and outcomes of ex vivo lung perfusion (EVLP) in this donor population. Methods: This was a retrospective study using a prospectively collected national registry. The United Network for Organ Sharing (UNOS) database was queried to identify adult patients who underwent lung transplantation between May 1, 2005, and December 31, 2021. Kaplan–Meier analysis and Weibull regression were used to compare survival in four cohorts (donation after brain death [DBD] with or without EVLP, and DCD with or without EVLP). The primary outcome of interest was patient survival. Results: Of the 21 356 recipients who underwent lung transplantation, 20 380 (95.4%) were from brain death donors and 976 (4.6%) from donors after circulatory death. Kaplan–Meier analysis showed no difference in the survival time between the two groups. In a multivariable analysis that controlled for baseline differences in donor and recipient characteristics, recipients who received lungs from cardiac death donors after EVLP had 28% shorter survival time relative to donor lungs after brain death without EVLP (hazard ratio [HR] 1.53, 95% confidence interval [CI] 1.10–2.15, p  = .01). Conclusions: The early survival differences observed after lung transplants from donors after circulatory death in lungs evaluated with EVLP deserves further investigation.